Afferent and Efferent Connections of the Cortex-Amygdala Transition Zone in Mice - Cádiz-Moretti, Bernardita; Abellán-Álvaro, María; Pardo-Bellver, Cecília; Martínez-García, Fernando; Lanuza, Enrique (Frontiers in Neuroanatomy, 2016)
The transitional zone between the ventral part of the piriform cortex and the anterior cortical nucleus of the amygdala, named the cortex-amygdala transition zone (CxA), shows two differential features that allow its identification as a particular structure. First, it receives dense cholinergic and dopaminergic innervations as compared to the adjacent piriform cortex and amygdala, and second, it receives projections from the main and accessory olfactory bulbs. In this work we have studied the pattern of afferent and efferent projections of the CxA, which are mainly unknown, by using the retrograde tracer Fluorogold and the anterograde tracer biotinylated dextranamine. The results show that the CxA receives a relatively restricted set of intratelencephalic connections, originated mainly by the olfactory system and basal forebrain, with minor afferents from the amygdala. The only relevant extratelencephalic afference originates in the ventral tegmental area (VTA). The efferent projections of the CxA reciprocate the inputs from the piriform cortex and olfactory amygdala. In addition, the CxA projects densely to the basolateral amygdaloid nucleus and the olfactory tubercle. The extratelencephalic projections of the CxA are very scarce, and target mainly hypothalamic structures. The pattern of connections of the CxA suggests that it is indeed a transitional area between the piriform cortex and the cortical amygdala. Double labeling with choline acetyltransferase indicates that the afferent projection from the basal forebrain is the origin of its distinctive cholinergic innervation, and double labeling with dopamine transporter shows that the projection from the VTA is the source of dopaminergic innervation. These connectivity and neurochemical features, together with the fact that it receives vomeronasal in addition to olfactory information, suggest that the CxA may be involved in processing olfactory information endowed with relevant biological meaning, such as odors related to reproductive or defensive behaviors.